PEMBUATAN PERENCANAAN BAHAN BAKU ATAU MRP (MATERIAL REQUIREMENT PLANNING) DAN KENDALA PADA PRODUKSI TAS ADIDAS FIBA1011 BULAN JANUARI DI PT.KOMITRANDO EMPORIO YOGYAKARTA - , DWIOCTA SYAFITRI, Yuni Wachid Asrori, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The methods of this study are literature study from relevant books to the topic, data collection from company, and interview with companyâs staffs. Raw material is the most important thing in the production process. Material Requirement Planning (MRP) is a company strategy for raw material planning, so that the company wouldnât shortage and excess of raw materials. Based on the results of this study concluded that the process that the process of making Material Requirement Planning (MRP) in PT. Komitrando Emporio requires two interrelated phases are Master Planning Schedule (MPS) and Bill of Materials (BOM). In the process of making the implementation of MRP there are still have problem. The problem is about how to manage the raw materials that the bag is still not well, because during the production process many raw materials that have been prepared depleted, disappear, and some raw materials has not arrived at this company.